Ground Flaxseed Supplementation Improved the Energy Utilization and Reduced Oxidative Stress in Buffalo Calves - Singh, Gurjinder; Singh, Gurpreet; Singh, Chanchal; Gupta, Ravikant (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted at the Department of Veterinary Physiology & Biochemistry and Animal Nutrition, College of Veterinary Science, Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana, Punjab, India during the period of October, 2018 to November, 2019 to evaluate the effect of ground flaxseed supplementation on blood biochemical and metabolic status of buffalo calves. The experiment was performed on four apparently healthy male buffalo calves of 2.0–2.5 years age in this present investigation. They were divided in 2 groups in a switch over design. The animals of Group I were kept as control. The animals of group II were supplemented with Ground Flaxseed @ 15% on dry matter basis replacing oil seed cakes in TMR for 21 days. Blood samples were collected at weekly intervals over a period of 21 days. The results revealed a significant (p<0.05) decrease in plasma glucose and cholesterol values in group II supplemented with ground flaxseed. There was no significant alteration with respect to the plasma total protein, triglycerides, creatinine, urea and total immunoglobulins in any of the groups. The erythrocytic lipid peroxidation was significantly reduced in the flaxseed supplemented group as compared to non-supplemented group. Thus, the present investigation revealed that flaxseed supplementation improved the energy utilization reduced the oxidative stress in animals.